Noite passiva dos sentidos e mediação mística : estudo do primeiro livro da noite escura de João da Cruz - Caberlon, Vinicius Fedrizzi (2024)
The present Master’s research intends to treat about the mysticism of John of the Cross, from the perspective of the 1st book of the Dark Night. Based on the bibliographical review carried out, it seeks to demonstrate that the sanjuanistic’s doutrine continues to be relevant to the delevopment of Christian spirituality in the contemporary world. The Spanish mystic is heir to a mystical tradiction, which uses an apophatic language to speak about the relationship between the human being and the Divine Mystery. The metaphor of the dark night emerges as an interesting and creative way to approach this issue. From a spiritual point of view, the dark night can be considered a painfull experience, in which the person feels a deep aridity because of the absence of God’s comforting touches. According to John of the Cross, the apparent absence of God, felt especially in situations of suffering and desolation, can be an indication that God is leading a person to a new stage of their spiritual journey. Thus, in developing the doctrine of the passive night of the senses, the Spanish mystic shines a ray of light on divine pedagogy and helps to understand that the aridity and desolation felt, may correspond to a calling to contemplate God’s action in a diferente way. The consequence of passing througt the passive night of the senses is a spiritual maturation, which elevates the human sensibility. By allowing oneself to be guided by trust in the presence and action of the Holly Spirit in every circumstance of life, the person ceases to seek the simple satisfection of desires and sensitive appetites, and learns to walk in faith, whith greater firmness, on the path of Christian virtues and the values of the Gospel of Jesus Christ